Incidence of Adverse Reactions to Medicinal Products in Josina Machel Central Hospital during the Year of 2014 - Mateus Sebastião João Fernandes; Héctor Lara Fernández; Vladimir Calzadilla Moreira; Ignacio Miguel Gomez Macineira; Mario Héctor Almeida Alfonso (Formifarma, LDA., 2016)
Introduction: The lack of knowledge regarding the incidence of adverse drug reactions in the hospital setting and their impact on morbidity and mortality is, nowadays, a major health problem in Angola. In the last years, notifications of adverse drug reactions have been practically null, namely at a hospital level. It is of great importance to characterize the incidence of adverse drug reactions occurring in a hospital setting, in order to implement measures towards improving the quality of healthcare services. Material and Methods: We conducted a descriptive, prospective observational study to characterize the incidence of adverse drug reactions (ADRs) in patients admitted to the Central Hospital "Josina Machel" in Luanda during the year 2014. An intensive monitoring through active search for adverse reactions possibly related with the drugs prescribed to patients was performed. Results: Of a total of 2041 hospitalized patients, 175 had adverse drug reactions. The incidence rate was 4.74% in the medicine service (n = 1077) and 12.86% in the therapy service (n = 964). A total of 209 adverse drug reactions were identified, averaging 1,2 adverse drug reactions per patient. The highest incidence rate of adverse drug reactions was recorded in patients aged between 18 and 35 years old, with 79 patients (45.14%). With regard to therapeutic class, it was found that antimicrobials were the drugs most commonly associated with adverse reactions, with 71 notifications (40.57%), followed by analgesics, antipyretics and anti-inflammatory steroids with 20,00%. Quinine and artesunate were the antimicrobials most frequently implicated in causing an adverse drug reaction, with 25 (14.29%) and 15 (8.57%) notifications respectively. In the group of anti-inflammatory drugs, diclofenac stood out with 13 notifications (7.43%). The most common clinical manifestations were skin rash, which corresponded to 23,44% of the total number of adverse drug reactions, followed by bleeding, which accounted for 8.6% of the number of adverse reactions registered (n = 18). Within the group of antimicrobials, antimalarials and cephalosporins were the drugs most commonly associated with skin lesions, with 27 notifications (55.10%). Most of adverse reactions were moderate in severity (66.86%) and were classified as probably drug-related (80.57%). Discussion and Conclusion: A high frequency of adverse drug reactions was found in hospitalized patients, particularly in the therapy service. It was evident the subnotification of adverse reactions by health professionals and the need for a system of notification of adverse reactions that combines passive and active surveillance for the prevention and detection of adverse drug reactions.